META ANALISIS PENGGUNAAN ALAT PERAGA TERHADAP PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA - Firdah Annisa; Maulidiya Maulidiya; Siti Rahmawati (Universitas Muhammadiyah Surabaya, 2022)
Learning outcomes are influenced by several factors including the use of teaching aids by educators in the teaching and learning process. The use of teaching aids in the learning process in elementary schools (SD) really helps improve understanding of concepts and skills in the subject matter taught, especially mathematics. The purpose of this research is to 1). Improving student learning outcomes in learning mathematics by using teaching aids, 2) The difference between student learning outcomes using teaching aids and student learning outcomes not using teaching aids. The research method used is descriptive analysis. The type of research used is a meta-analysis by reviewing several articles and journals from previous studies. Data collection in this study was carried out by browsing articles and journals on several electronic media. Data analysis used quantitative analysis in the form of percentages and qualitative analysis which contained a description of the findings in the study. Based on research data carried out by meta-analysis, it can be concluded that the use of teaching aids in learning mathematics in elementary schools has been widely used by previous researchers, this media can improve student learning outcomes with an average of 79.7 and the previous value with an average of 62, 58, This is declared successful because of the increase in student learning outcomes in learning mathematics in elementary schools.Â Keywords: Props; learning outcomes; mathematics.